A Continuum of Evidence on Evidence-Based Programs: A New Resource for Use in Military Social Service Delivery. (2nd October 2017) - Karre, Jennifer K.; Perkins, Daniel F.; Aronson, Keith R.; DiNallo, Jennifer; Kyler, Sandee J.; Olson, Jonathan; Mentzer, C. Eddy
ABSTRACT: Evidence-based programs can promote well-being; however, barriers to implementation exist. Barriers include lack of time to find evidence and lack of expertise among some practitioners in reading and evaluating evidence. A partnership among the Department of Defense Office of Military Community and Family Policy, the National Institute for Food and Agriculture, and Pennsylvania State University resulted in the development of a new information repository. The Clearinghouse for Military Family Readiness at Penn State (Clearinghouse) and the Clearinghouse's Continuum of Evidence (Continuum) were designed to assist professionals in identifying evidence-based programs that can improve the well-being of military families (http://www.militaryfamilies.psu.edu ). The development of the Continuum included reviews of existing rating systems, expert review, practical review, and inter-rater agreement checks. The Clearinghouse contains information on over 1, 000 programs relevant to both civilian and military families. Topics include parenting, coping and resilience, child behavior, obesity, alcohol and substance use prevention, and mental health treatment; target audiences include children, youth, adults, and families. Empirical evidence and systematized criteria are used to place programs as Effective (Randomized Control Trial), Effective (Quasi-experimental), Promising, Unclear (+), Unclear (ø), Unclear (−), or Ineffective. The Clearinghouse provides information and encourages professionals to make informed decisions based on their needs and resources.